2013
DOI: 10.1370/afm.1475
|View full text |Cite
|
Sign up to set email alerts
|

Quality, Satisfaction, and Financial Efficiency Associated With Elements of Primary Care Practice Transformation: Preliminary Findings

Abstract: PURPOSE We examined quality, satisfaction, fi nancial, and productivity outcomes associated with implementation of Care by Design (CBD), the University of Utah's version of the patient-centered medical home. METHODSWe measured the implementation of individual elements of CBD using a combination of observation, chart audit, and collection of data from operational reports. We assessed correlations between level of implementation of each element and measures of quality, patient and clinician satisfaction, fi nanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 4 publications
1
47
2
Order By: Relevance
“…23 We found that most employees in all roles felt that PACT's recommended four-person team structure did work well, once in place. Our study's finding that Clinical and Clerical Associates in particular found increased job satisfaction within team-based care is interesting, in light of Day and colleagues' 8 finding that continuity and engagement in the Medical Assistant role was associated with several positive PCMH outcomes. Similarly, Gabbay and colleagues 24 found that an expanded medical assistant role was characteristic of higher performing PCMH practices.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…23 We found that most employees in all roles felt that PACT's recommended four-person team structure did work well, once in place. Our study's finding that Clinical and Clerical Associates in particular found increased job satisfaction within team-based care is interesting, in light of Day and colleagues' 8 finding that continuity and engagement in the Medical Assistant role was associated with several positive PCMH outcomes. Similarly, Gabbay and colleagues 24 found that an expanded medical assistant role was characteristic of higher performing PCMH practices.…”
Section: Discussionmentioning
confidence: 64%
“…4 Medical home features, such as enhanced patient access, improved scheduling, care provider continuity, and care coordination activities, have been associated with lower rates of avoidable hospitalizations and decreased Emergency Department use. [5][6][7][8] Multiple difficulties in implementing the PCMH model, however, have been documented. The move away from a physician-centric model of care towards one that is truly team-oriented, and the challenges of aligning financial reimbursement with the PCMH's emphasis on proactive prevention, are only two of the model's persistent challenges across diverse primary care practices.…”
Section: Introductionmentioning
confidence: 99%
“…21,24,25 Many patients, especially those with complex medical and social needs, may find the patient-centered team approach more convenient and efficient. Those who do not will likely vote with their feet as long as they are able.…”
Section: Discussionmentioning
confidence: 99%
“…To date, qualitative studies of PCMH implementation have looked primarily at small, nonacademic practices with ten or fewer physicians, [16][17][18][19] and, with one exception, 19 have not focused on differences by practice size. [20][21][22] Few have assessed implementation in academic clinics. 23,24 Therefore, we conducted a qualitative case study within a large VHA academically affiliated primary care clinic to understand the experiences of primary care leadership, physicians, and staff during early PACT implementation, and to provide insights to help guide future PCMH implementation initiatives.…”
Section: Introductionmentioning
confidence: 99%